Directions for improving the quality of secondary ambulatory medical aid to the Ukrainian population - Kravchenko, V. V. (Journal of Education, Health and Sport, 2018)
Purpose: to conduct a systemic comparative analysis of the activities of municipal and private outpatient clinics (OC) providing secondary medical care, identify problem areas and ways to increase the population's satisfaction with the quality of medical care. Methods: Methods of the system approach and analysis, sociological, medical and statistical method, method of expert estimations had been applied in this research. The sociological research was conducted in 2017 according to a specially developed program and involved 437 patients, 411 doctors in community OC and 396 patients, 106 doctors in private OC inKiev. Expert assessment of the state of the organization of outpatient care was carried out by 21 highly qualified experts. Results: On the results of comparative analysis of the activities of public and private OC had been determined that the population is not satisfied with the existing organization of work of public OC. The development of outpatient care depends on the level of funding, management quality, effective planning, organization of production, and the introduction of public-private partnership (PPP) mechanisms . Conclusions In the current economic conditions priority in optimizing the activity of the municipal OC to improve the population's satisfaction with the quality of medical care is the transition of the OC to the principles of PPP.